A cartografia do litoral paranaense - Ricardo Rodrigues Monteiro; André Nagy (Confins)
In this work we present the Cartography of varied themes of the coast of Paraná, predominantly for the 2010 census and on the scale of all census tracts. The cartographic representation method included the use of free software, especially the Philcarto application, for the thematic maps, Carte &Données, for the flow maps, Inkscape, for the edition of the exported images of Philcarto, and GIMP, for the final edition images. The texts were written in order to be accessible to both specialist and non-specialist readers. We sought a general representation of themes such as: territorial formation and population growth of coastal municipalities, since 1872, demographic by age groups and population projection for 2015, age groups and sex of students enrolled in UFPR Litoral between 2008 and 2016, enrollments in the school network and the distance-time displacements for access to universities, declivities and map of urban and rural sectors according to the IBGE classification, permanent private households and unoccupied domiciles for occasional use (second residences), the average number of inhabitants per household and the population density and sex ratio. The intention is to help the planning actions by public institutions and to feed with data and cartographic information the discussions in teaching, research and extension at all scales of local public and / or private education.